A diagnostic pitfall of a sternal mass. Issue 7 (21st July 2021) - Abid, Walid; Hentati, Abdessalem; Ben Halima, Ghassen; Rebai, Mohamed; Lasmar, Ahmed; Gouiaa, Naourez; Frikha, Imed
Abstract: Primary sternal lymphoma represents a rare entity which must be evoked in front of a sternal mass especially as its treatment is different from that of sarcomas, the principal etiology of sternal masses. Abstract : Primary sternal lymphoma represents a rare entity which must be evoked in front of a sternal mass especially as its treatment is different from that of sarcomas, the principal etiology of sternal masses.